State Responsibility Towards Abandoned Children in the Concept of Legal Certainty - Bambang Tri Bawono; Moh Nurul Huda (Jurnal Pembaharuan Hukum, 2026)
The threat of neglected children's lives is one of the important things that must be paid attention to. This is because children are the next generation of the nation who are thirsty for their rights as stipulated in Article 34 paragraph (1) of the 1945 Constitution. Data from the social services still shows the number of neglected children, so that social rehabilitation efforts as stipulated in the Minister of Social Affairs are very important to be continuously implemented. The type of research used in this study is normative legal research with research specifications using analytical descriptive. The results of the study show that the responsibility for maintaining and improving the standard of living for neglected children, including street children, beggars and vagrants, is part of the state's obligations as mandated by the Constitution. With this mandate, the government also carries out several instruments to maintain and overcome neglected children. One of the maintenance instruments carried out is conducting raids. In this context, raids are a threat to neglected children because of the fear that if they are arrested they will receive criminal sanctions under Articles 504 and 505 of the Criminal Code because most of their lives come from begging and vagrancy. Therefore, efforts to care for abandoned children need to be carried out in a humane manner, aiming to develop a way of thinking and attitude to live as they should.